'I don't care whether it's HPV or ABC, I just want to know if I have cancer.' Factors influencing women's emotional responses to undergoing human papillomavirus testing in routine management in cervical screening: a qualitative study. (1st April 2014) - O'Connor, M; Costello, L; Murphy, J; Prendiville, W; Martin, CM; O'Leary, JJ; Sharp, L; the Irish Screening Research Consortium (CERVIVA)
<x xml:space="preserve">Abstract</x> Objective To explore emotional responses, and predictors of negative reactions, among women undergoing human papillomavirus (HPV) tests in routine clinical practice. Design Exploratory qualitative interview study. Setting A large busy colposcopy clinic in a Dublin hospital. Sample Twenty‐seven women who had had an HPV DNA test in the previous 6 months following one or more low‐grade cytology tests or treatment for cervical intraepithelial neoplasia (CIN). Methods In‐depth semi‐structured interviews were conducted. Interview transcripts were analysed using a thematic approach (Framework Analysis). Main outcome measures Women's emotional responses and predictors of negative emotional reactions. Results For most women, having a test for high‐risk HPV types generated little negative or positive emotional impact. Adverse emotional responses related to HPV infection rather than testing. Factors that influenced whether women experienced negative emotional responses were: concerns over abnormal cytology or diagnosis of CIN; HPV knowledge; awareness of HPV being sexually transmitted; awareness of HPV prevalence; and HPV information needs. Women's concerns about abnormal cytology/CIN dominated all other issues. Conclusions These qualitative data suggest that in the context of follow up of abnormal cytology or treatment for CIN, the emotional impact of HPV testing may be modest: women's primary concerns at this time relate to abnormal cytology/CIN.